Guinea Pig Models of Asthma. Issue 1 (1st December 2014) - McGovern, Alice E.; Mazzone, Stuart B.
Abstract: Described in this unit are methods for establishing guinea pig models of asthma. Sufficient detail is provided to enable investigators to study bronchoconstriction, cough, airway hyperresponsiveness, inflammation, and remodeling. © 2014 by John Wiley & Sons, Inc.